Urgensi Pembentukan Lembaga Valuasi Kekayaan Intelektual dalam Kerangka Hukum Pengawasan untuk Mewujudkan Tata Kelola Ekonomi Berbasis Inovasi - Yemima Angelika (Lembaga Pengembangan Kinerja Dosen, 2026)
Intellectual property (IP) holds strategic value as an intangible asset that plays a crucial role in the growth of a knowledge-based national economy. However, the optimal use of IP as an object of economic security remains hampered by the absence of a dedicated institution to assess and guarantee the economic value of IP. This paper highlights the urgency of establishing an IP valuation institution that not only plays a role in determining asset values ​​but also carries out oversight functions to ensure credibility, legal protection, and fair access to financing, particularly for MSMEs and creative industry players. In the context of oversight law, the existence of this institution is crucial to ensure the implementation of the IP guarantee system adheres to the principles of accountability, transparency, and effectiveness. The application of the Whole of Government approach is also discussed as an integrative strategy for building synergy between the agencies involved. Thus, the establishment of this institution not only addresses economic and legal needs but also serves as a modern oversight instrument for national IP governance.